Cable Tension Preslack Method Construction Simulation and Engineering Application for a Prestressed Suspended Dome. (11th October 2015) - Liu, Xuechun; Zhang, Ailin; Fu, Wanlin
Abstract : To solve the shortage of traditional construction simulation methods for suspended dome structures, based on friction elements, node coupling technology, and local cooling, the cable tension preslack method is proposed in this paper, which is suitable for the whole process construction simulation of a suspended dome. This method was used to simulate the construction process of a large-span suspended dome case study. The effects on the simulation results of location deviation of joints, construction temperature, construction temporary supports, and friction of the cable-support joints were analyzed. The cable tension preslack method was demonstrated by comparing the data from the construction simulation with measured results, providing the control cable tension and the control standards for construction acceptance. The analysis demonstrated that the position deviation of the joint has little effect on the control value; the construction temperature and the friction of the cable-support joint significantly affect the control cable tension. The construction temperature, the temporary construction supports, and the friction of the cable-support joints all affect the internal force and deflection in the tensioned state but do not significantly affect the structural bearing characteristics at the load state. The forces should be primarily controlled in tensioned construction, while the deflections are controlled secondarily.